Uruguay : Poverty and Social Impact Assessment of the Tax Reform - World Bank (Washington, DC, 2012)
The Poverty and Social Impact Assessment (PSIA) analyzes the impact of the tax reform, which came into effect in July 2007, on tax incidence and poverty in Uruguay. The essence of the reform is the introduction of a dual personal income tax, which taxes labor income at progressive rates and capital income at lower, proportional rates. A further modification is the reduction in the revenue share of indirect taxes. The study aims to provide information to inform policy discussion on distributional implications of tax reform. In addition, it gives impetus for further more sophisticated analysis of current and proposed tax reforms. In designing a tax system, a trade-off exists between efficiency, equity and administrative simplicity. The paper focuses on one aspect of this trade-off by evaluating the equity impact of the tax reform in Uruguay. Neither the efficiency of the post-reform tax system nor the effect on tax administration is examined. Assessing the distributional impact of a tax reform is important, firstly, as there is a potential to mitigate the equity-efficiency trade-off in the design of tax structures, and secondly, as the expenditure side of the budget can then be employed to diminish any adverse distributional impacts.